Macroeconomics : income and monetary theory - Aschheim, Joseph; Hsieh, Ching-Yao (Columbus, Ohio: C. E. Merrill Pub. Co., 1969)
This book is designed to fill a specific need of the first-year graduate student and advanced undergraduate in economics because it highlights post-Keynesian developments income and monetary theory and relevant theoretical antecedents. It also includes a systematic treatment of the relevant historical antecedents of contemporary income and monetary theory.
Includes index
Includes bibliographical reference
usc 4/8/17
Loans
Keywords: Macroeconomics; Economics; Monetary theory; Keynesian economics